Teachers as Digital Facilitators: A Qualitative Study on Professional Adaptation in Technology-Based Curriculum - Garry Brumadyadisty; Siska Armawati Sufa; Gardena Smoro Laksmi; Suprayitno Suprayitno (SERUMPUN : Journal of Education, Politic, and Social Humaniora, 2025)
The development of digital technology has driven significant changes in educational practices, particularly in the role of teachers, who have transformed from knowledge deliverers to digital facilitators. This study stems from the problem of low pedagogical readiness and institutional support experienced by teachers in facing the demands of technology-based learning. The purpose of this study is to analyze the process of reconstructing teachers' professional identities, supporting and inhibiting factors, and their implications for pedagogical practices in the digital era. The research methodology used a qualitative approach with NVivo-assisted thematic analysis, involving in-depth interviews with teachers from various school contexts. The results show that the changing role of teachers requires cognitive, emotional, and social adjustments. Self-efficacy proved to be a central factor in successful adaptation, while infrastructure limitations and ambiguous administrative policies caused emotional stress. Peer collaboration and reflective practices strengthen resilience and serve as sources of pedagogical innovation. The study concludes that digital adaptation is not merely a technical skill, but a process of reconstructing pedagogical identity influenced by internal agency, social structures, and institutional support. Recommendations include strengthening continuous training, equitable infrastructure policies, and establishing teacher practice communities to support sustainable transformation.